An inhibitory peptide derived from the α-subunit of the epithelial sodium channel (ENaC) shows a helical conformation - Härteis, Silke; Schaal, Daniel; Brauer, Felix; Brueschke, Stefan; Schweimer, Kristian; Rauh, Robert; Sticht, Heinrich; Roesch, Paul; Schwarzinger, Stephan; Korbmacher, Christoph (Cellular Physiology and Biochemistry, 2012)
Proteolytic activation of the heteromeric epithelial sodium channel (ENaC) is thought to involve the release of inhibitory peptides from the extracellular domains of its ?- and ?-subunit. Recently, we demonstrated that an ?-13-mer peptide, corresponding to a putative inhibitory region within the extracellular domain of human ?ENaC, inhibits human ???ENaC. The aim of the present study was to investigate the structural basis of the inhibitory effect of this ?-13-mer peptide. Analysis of the peptide by replica exchange molecular dynamics method, circular dichroism spectroscopy, nuclear magnetic resonance spectroscopy, and molecular dynamics simulations suggested that a helical turn at the carboxy-terminus is the preferred conformational state of the ?-13-mer peptide. From this we predicted that a specific mutation (leucine 188 to alanine) should have a strong effect on the conformational preferences of the peptide. To functionally test this, we compared the effect of the wild-type ?-13-mer with that of a mutant ?-L188A-13-mer on ENaC currents in Xenopus laevis oocytes heterologously expressing human ???ENaC. We demonstrated that replacing the leucine 188 by alanine abolished the inhibitory effect of the ?-13-mer peptide on ENaC. These findings suggest that a helical conformation in its carboxyterminal part is functionally important to mediate ENaC inhibition by the ?-13-mer peptide. However, high resolution structural information on the complex of the inhibitory ?ENaC peptide and the channel are needed to confirm this conclusio
EVALuna2:4484